Odor, air quality, and well-being: understanding the urban smellscape using crowd-sourced science - Sahil Bhandari; Davi de Ferreyro Monticelli; Karen Xie; Andre Ramkairsingh; Rochelle Maher; Angela Eykelbosh; Sarah B Henderson; Naomi Zimmerman; Amanda Giang (IOP Publishing, 2024)
Odors are a topic of emerging environmental health interest given their potential links to air quality, health, well-being, and quality of life. However, odors have traditionally been challenging to study given variability in individual sensitivity and perception, atmospheric physico-chemical processes, and emissions of mixtures of odorous contaminants. Here, we explore the potential utility of crowd-sourced odor report data in improving understanding of spatiotemporal patterns of odor experiences and their impacts. We conduct quantitative and qualitative analyses of a 12-month data set from a web application collecting crowd-sourced odor reports, including spatiotemporal information, odor and self-reported impacts description (OSAC: odors, symptoms, actions in response, and suspected causes), and demographics, in Vancouver, Canada. Users report diverse OSAC with strong seasonality and spatial variability. Reported symptoms, ranging from neurological to emotion- and mood-related, highlight the complexity of odor-related health and well-being impacts. Odors can trigger maladaptive actions, where individuals are exposed to other environmental stressors (e.g. heat stress) or curtail healthy behaviors (e.g. exercising outside) to cope with odor impacts. Clustering analysis of OSAC suggests that odor exposures may be linked to health, well-being, and quality of life impacts through complex mechanisms, related not only to the odor experienced but also perceived causes. Spatiotemporal patterns in reports highlight the potential influence of persistent sources (e.g. waste management) and transient events (e.g. accidents). Exploratory multiple linear regression models suggest that monitoring of air quality and meteorology may be insufficient to capture odor issues. Overall, these results suggest that crowd-sourced science incorporating self-reported health and well-being effects and behavioral responses can enrich understanding of the impacts of odorous emissions at large spatiotemporal scales and complement traditional air pollution monitoring.